Pengaruh Keragaman Gender Dewan, Industri dan Ukuran Perusahaan terhadap Donasi Corporate Social Responsibility - Ayu Indriyani, Dwi; Sudaryati, Erina (E-Jurnal Akuntansi; Vol 30 No 8 (2020), 2020)
Business developments that embrace the concept of a triple bottom line (TBL) encourage companies to pay attention to environmental and social challenges rather than just focus on maximum profits. Companies must contribute by making donations in corporate social responsibility activities or known as corporate philanthropy as a form of accountability to stakeholders. Research on the factor of board gender diversity, industry type and company size on CSR donations. This research uses multiple regression method. The research sample uses companies listed on the Indonesia stock exchange period 2017-2018. The results showed that the board gender diversity and the type of industry had a significant effect on CSR donations, while the size of the company had no significant effect. Keywords: Board Gender Diversity; Firm Size; Industry Type; Donation On Corporate Social Responsibility.